Pengembangan Karakter Jujur Melalui Pembiasaan - Juliana Batubara (Jurnal Konseling dan Pendidikan, 2015)
Honesty is a the important character in the student. The creation of this character takes quite a long time and  cannot be conducted in an instant. Honest character can be developed using the behavioristik theory by conditioning with stimulus-response technique-reinforcement. The role of teacher, counselors, other school personnel, parents and the community are very important in the development of the student’s characters through conditioning.